Complete mitochondrial genome of the Amur leopard (Panthera pardus orientalis Schlegel, 1857) - Jung A Kim; Hye Sook Jeon; Je Hoon Jeon; Soonok Kim; Junghwa An (Mitochondrial DNA. Part B. Resources, 2019)
This study sequenced the complete mitochondrial genome of the female Amur leopard (Panthera pardus orientalis) using highest-quality (310× average coverage depth) big cat reference genomes. The total genome length was 16,964 base pairs, consisting of 13 protein-coding genes, 2 rRNAs, 22 tRNAs, and 1 control region. Phylogenetic analysis using protein-coding regions revealed that a P.p.orientalis was closely related to the P. pardus clade.